2001
DOI: 10.1016/s0014-5793(01)02835-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional reconstitution of Arabidopsis thaliana plant uncoupling mitochondrial protein (AtPUMP1) expressed in Escherichia coli

Abstract: The Arabidopsis thaliana uncoupling protein (UCP) gene was expressed in Escherichia coli and isolated protein reconstituted into liposomes. Linoleic acid-induced H+ fluxes were sensitive to purine nucleotide inhibition with an apparent K(i) (in mM) of 0.8 (GDP), 0.85 (ATP), 0.98 (GTP), and 1.41 (ADP); the inhibition was pH-dependent. Kinetics of AtPUMP1-mediated H+ fluxes were determined for lauric, myristic, palmitic, oleic, linoleic, and linolenic acids. Properties of recombinant AtPUMP1 indicate that it rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 31 publications
(79 reference statements)
2
33
0
1
Order By: Relevance
“…We showed that StUCP yeast mitochondria exhibited a diminished resting potential and a high sensitivity to uncoupling by LA. The StUCP-dependent uncoupling activity measured in yeast (expressed as LA-stimulated oxidation rate) was similar in mitochondria from yeast expressing StUCP (this work) and mammalian UCP2 (16) (7,29). StUCP protonophoric activity in yeast mitochondria is also in agreement with the ability of plant UCP reconstituted in proteoliposomes to collapse the proton gradient, as evidenced with AtUCP1 expressed in E. coli (7) or with the PUMP fraction isolated from potato mitochondria (1,30).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We showed that StUCP yeast mitochondria exhibited a diminished resting potential and a high sensitivity to uncoupling by LA. The StUCP-dependent uncoupling activity measured in yeast (expressed as LA-stimulated oxidation rate) was similar in mitochondria from yeast expressing StUCP (this work) and mammalian UCP2 (16) (7,29). StUCP protonophoric activity in yeast mitochondria is also in agreement with the ability of plant UCP reconstituted in proteoliposomes to collapse the proton gradient, as evidenced with AtUCP1 expressed in E. coli (7) or with the PUMP fraction isolated from potato mitochondria (1,30).…”
Section: Discussionsupporting
confidence: 76%
“…In addition, various cDNAs coding for putative UCPs were identified in plants such as potato, Arabidopsis thaliana, and skunk cabbage (Symplocarpus foetidus), a thermogenic plant from the Aracea family (3)(4)(5)(6). Recently, the Arabidopsis thaliana AtUCP1 gene was expressed in Escherichia coli and the isolated protein reconstituted into liposomes (7). Like mammalian UCPs, the plant UCP 1 requires free fatty acids for its activity and is inhibited by purine nucleotides (GDP, ATP, GTP, or ADP) (7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is now apparent that UCPs are encoded by small gene families, although consensus on the precise composition of these families has not yet been reached (9,10). Plant UCPs appear to be regulated in a similar fashion to their mammalian counterparts; they catalyze a fatty aciddependent, nucleotide-inhibitable proton conductance (11)(12)(13) and are activated by superoxide and aldehyde products of lipid peroxidation (14,15). Given that formation of superoxide and related reactive oxygen species (ROS) by the respiratory chain is increased nonlinearly at high mitochondrial membrane potential, activation of UCP by superoxide represents a feedback loop by which superoxide production can be regulated.…”
mentioning
confidence: 99%
“…UCP-like activity has been observed in isolated mitochondria from a number of plant species and the potato UCP activity has been purified and its proton transport properties recovered by reconsitution into liposomes (18). Furthermore, reconstitution of the AtUCP1 gene product into liposomes has provided the first link between a plant UCP gene and proton transport activity (19). However, a recent study has shown that when care is taken to avoid artifacts caused by extraneous effects of nucleotides on other electron transport chain components, the fatty acid-stimulated proton leak of potato mitochondria is not inhibited by nucleotides (20).…”
mentioning
confidence: 99%